The Effect of Hedonic Shopping Motivation, Shopping Lifestyle, and Fashion Involvement on Impulse Buying on Zalora Customers in Medan City - Annisa Edelia; Tuti Anggraini (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to analyze the direct effect of Hedonic Shopping Motivation, Shopping Lifestyle, and Fashion Involvement on Impulse Buying. The population of this research is Zalora's customers in Medan city. With an unknown population, Bernoulli's formula is used and the number of samples is 60 respondents by purposive sampling. Data obtained by questionnaire google forms. The data analysis method used is associative statistical analysis and Partial Least Square (SEM-PLS) 3.0 analysis. Data collection techniques using a Google form questionnaire. The results show that the Hedonic Shopping Motivation variable has a significant effect on Impulse Buying, the Shopping Lifestyle variable has a significant effect on Impulse Buying and the Fashion Involvement variable has a significant effect on Impulse Buying.